Integrating MTTR, FMEA and Criticality Matrix Analysis for Enhancing Maintenance Strategy in the Ice Cream Industry: A Case Study in Indonesia - Dede Roni; Elaeys Mulia Bulqis (Asian Journal of Multidisciplinary Research, 2026)
In the highly competitive ice cream manufacturing industry, production line stability is critical due to the vulnerability of perishable materials. One of the main challenges faced by companies is the high frequency of machine downtime, which disrupts production targets, increases energy consumption, and elevates the risk of raw material waste. This study aims to evaluate repair speed performance across production lines based on the Mean Time to Repair (MTTR) tolerance limit, identify and prioritize critical failure modes using the Risk Priority Number (RPN), and formulate maintenance strategy recommendations by classifying assets into three criticality levels: High, Medium, and Low. The analysis results indicate that lines 4, 8, and 9 are the most critical production areas, as their performance exceeds the company’s MTTR tolerance limit of 40 minutes. The highest average MTTR values were recorded on line 4 (46.67 minutes), line 8 (42.57 minutes), and line 9 (65.00 minutes). These results are supported by the Failure Mode and Effects Analysis (FMEA), where the highest RPN values were identified on the molding machine in line 4 (RPN 140 and 100), the tunnel machine in line 8 (RPN 100), and the tunnel machine in line 9 (RPN 100). Furthermore, the Criticality Matrix consistently positions line 4 and line 9 within the High Criticality zone, indicating that failures on these lines have a significant impact on production flow and therefore require immediate maintenance prioritization compared to assets in the medium and low risk categories. Based on this risk mapping, the study recommends a strategic transition from reactive maintenance toward a differentiated maintenance policy, including the implementation of Condition Based Maintenance (CBM) on critical lines and the standardization of maintenance Standard Operating Procedures (SOPs). This approach is expected to improve equipment reliability, reduce unplanned downtime, and support the long term sustainability of production quality.